Development of Water Debit Measuring Instruments as Physics Learning Media Using a Flow Meter Sensor - Tomi Putra Wijaya; Janariani Janariani; Supardi Supardi (Universitas Lambung Mangkurat, 2023)
Physics learning aims to ensure that students understand physics concepts completely. Understanding of the concept can be achieved through the help of learning media in the form of teaching aids from physics materials. This research aims to develop learning media for measuring water discharge using a flow meter sensor to improve students' conceptual understanding of dynamic fluid material. This research includes development research through the ADDIE model, carried out until the development stage. Data collection techniques are carried out through the calibration of measuring instruments. The technique for data analysis used is the descriptive analysis of proportions. The study results obtained the following results: 1) The calibration results show that the water discharge measuring instrument as a learning medium has a very small error rate, and 2) The results of the validity assessment obtained by the water discharge measuring instrument have high validity. The water debit measuring instruments can be used to increase understanding of the dynamic fluid material concept. Using this air discharge measuring instrument will help students understand the concept of fluid dynamics, especially in air discharge subjects.